Simple, Implementable Fiscal Policy Rules - Kumhof, Michael (IMF Working Papers; Working Paper ;, 2009)
This paper analyzes the scope for systematic rules-based fiscal activism in open economies. Relative to a balanced budget rule, automatic stabilizers significantly improve welfare. But they minimize fiscal instrument volatility rather than business cycle volatility. A more aggressively countercyclical tax revenue gap rule increases welfare gains by around 50 percent, with only modest increases in fiscal instrument volatility. For raw materials revenue gaps the government should let automatic stabilizers work. The best fiscal instruments are targeted transfers, consumption taxes and labor taxes, or, if it enters private utility, government spending. The welfare gains are significantly lower for more open economies.